2021
DOI: 10.1007/s00170-021-07040-3
|View full text |Cite|
|
Sign up to set email alerts
|

Geometrical optimization of centerless grinding process by profiled workrest

Abstract: This work presents a method to optimize centerless grinding geometrical configuration. It is based on the regulation of the horizontal axes of operating and regulating wheels of the machine, coupled with an opportune blade profile, allowing a continuous selection of workrest angle and workpiece height, without requiring blade substitution and/or manual interventions. The regulation of workrest angle and height cannot be done independently: their relationship is defined during blade profile design. In machines … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The center height refers to the distance from the center of the workpiece to the line between the center of the grinding wheel and the regulating wheel, and the support plate angle is the angle between the supporting surface of the plate and the vertical direction, as shown in Figure 2 . Some research has shown that the harmonic height and wavelength of the roundness profile change with the above two factors [ 32 , 33 , 34 ]. Therefore, this paper designed the machining experiments with different support plate angles and different center heights, and the values of the parameters are shown in Table 1 .…”
Section: Influence Of Centerless Grinding Process Parameters On Profilementioning
confidence: 99%
“…The center height refers to the distance from the center of the workpiece to the line between the center of the grinding wheel and the regulating wheel, and the support plate angle is the angle between the supporting surface of the plate and the vertical direction, as shown in Figure 2 . Some research has shown that the harmonic height and wavelength of the roundness profile change with the above two factors [ 32 , 33 , 34 ]. Therefore, this paper designed the machining experiments with different support plate angles and different center heights, and the values of the parameters are shown in Table 1 .…”
Section: Influence Of Centerless Grinding Process Parameters On Profilementioning
confidence: 99%
“…The articles by Wu et al (2005), Prilutskii and Parfenov (2021), Otaghvar et al (2019) and Brzhozovskii and Zakharov (2015), examined the geometric and kinematic aspects of setting up the centerless grinding machines. Articles by Leonesio et al (2021), Barrenetxea et al (2018), Yan et al (2017), Alvarez et al (2020) and Bianchi et al (2020) is devoted to the study of dynamic processes in the grinding machines. The articles by Brecher and Hannig (2008), Cui et al (2014) and Yao et al (2021) noted that the greatest problem in the manufacture of bearing parts is ensuring the minimum roundness of the part.…”
Section: Introductionmentioning
confidence: 99%
“…The angle and position of the workpiece cannot be regulated independently because their relationship is defined in the blade design. As a result of the research, the optimum choice of machining parameters can be made, which also makes it possible to reduce machining times [ 24 ].…”
Section: Introductionmentioning
confidence: 99%